Open Innovation Challenge as a new strategic Instrument for the public sector - González de Uña, Ovidio J.; Carballar Rincón, Alejandro; Soler Regli, María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2018)
Open innovation challenges are a challenging tool that allows institutions and organizations to access external talent and to boost their innovation processes. Being widely used in past centuries, they get out of use throughout the twentieth century due to the rise of patents. However, due to the possibilities currently offered by the Internet the private sector is using them again with remarkable success. This work uses the scientific method to analyse the new potential offered by open innovation challenges, and how these can be adapted to the public sector to incorporate them as a novel strategic instrument that stimulates innovation, fosters synergies with the private sector and promotes development of new market niches.